Effect of mixing ratio on the adsorption behavior of low-rank coal surface using mixed collectors: Experimental and molecular dynamics simulation study. Issue 9 (2nd September 2022) - Liu, Zechen; Ren, Hourui; Yang, Zhe; Liao, Yinfei; Wang, Yongtian
ABSTRACT: The effect mechanism of mixing ratio on the adsorption behavior of low-rank coal surface using mixed collectors has not been systematically studied. In this study, dodecane (D) and n-valeric acid (N) were mixed into different collectors in different ratios, and their adsorption mechanism on the surface of LRC was studied by experiment and simulation calculation. The flotation results indicated that the sequence of the flotation clean coal yield was 8:2 > 6:4 > 5:5 > 7:3 > 9:1. The measurement results of the heat of adsorption, total organic carbon, and liquid phase contact angle all responded to the flotation results as a whole. The molecular dynamics simulation results revealed that when an appropriate ratio was used to form a mixed collector, the N molecules could make the D molecules form oil molecular layer thicken, thus increasing the hydrophobicity of the surface of the LRC molecules. The optimal mixing ratio could also create a large interaction energy between the mixed collector and LRC. Therefore, D and N need to be mixed at a proper ratio to maximize the LRC flotation efficiency.